Melodrama and Social Crisis: The Mysteries of Paris and the Politics of Slavery in the Brazilian Empire (c. 1840-1850) - El Youssef, Alain; Mayor, Mariana França Soutto [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2023)
On March 25, 1851, the anniversary of the Brazilian Constitution of 1824, the Teatro São Pedro de Alcântara presented, under the eyes of Emperor Pedro II, the play The Mysteries of Paris. The play was based on the homonymous novel by French writer Eugène Sue, translated into Portuguese by Justiniano José da Rocha in the 1840s. The article analyzes the motivations of the translation shortly after its original publication and its theatrical presentation in the early 1850s. Based on newspapers of the time, sources from the National Dramatic Conservatory, and specialized bibliography, the text argues that both the translation and the staging of the play were part of a strategy that made up the politics of slavery carried out by the Saquaremas between the Regency and the beginning of the Second Reign.
MELODRAMA E CRISE SOCIAL: OS MISTÉRIOS DE PARIS E A POLÍTICA DA ESCRAVIDÃO NO IMPÉRIO DO BRASIL (C. 1840-1850)
Keywords: Politics of slavery; São Pedro de Alcântara Theater; The Mysteries of Paris